Physiognomy and Comic Ugliness in the Political Cartoons of Enrique Hine - Baltodano Román, Gabriel (2016)
This article addresses political cartoons, and focuses on the ideological meaning constructed using two procedures found in political protest satire against the Costa Rican liberal Ricardo Jiménez-Oreamuno. They include the physiognomical comparison (with mythical figures and animals) and comic ugliness (Bergson) as mental, moral and intellectual rigidity. This study examines on the caricatures of the graphic artist Enrique Hine-Saborío , editor of the comic Costa Rican newspaper El Cometa.